1983
DOI: 10.1007/bf00542218
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of hydrochlorothiazide in relation to renal function

Abstract: The pharmacokinetics of hydrochlorothiazide (HCT) was investigated in 23 subjects with normal renal function or widely varying degrees of renal failure. The half-life of elimination increased from 6.4 h in subjects with normal renal function to 11.5 h in patients with mild renal impairment (endogenous creatinine clearance between 30 and 90 ml/min), and to 20.7 h in patients with an endogenous creatinine clearance below 30 ml/min. The cumulative urinary excretion and the renal HCT clearance were correspondingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 11 publications
0
20
0
1
Order By: Relevance
“…The addition channel, of tetraethylammonium, another inhibitor of the K CA channel in the abolished this effect, further implicating the K CA mechanism of dilation [22]. It is important to note that the thiazide doses used in these infusions resulted in plasma concentrations of 11 μg/ml, which is approximately 10–20 times the plasma concentration found in patients clinically treated with thiazides [23,24]. Moreover, these findings were contrary to previous studies, which did not find any vasoactivity in the human forearm, although such studies used doses more comparable to those found in clinical practice [25,26].…”
Section: Antihypertensive Effectsmentioning
confidence: 99%
“…The addition channel, of tetraethylammonium, another inhibitor of the K CA channel in the abolished this effect, further implicating the K CA mechanism of dilation [22]. It is important to note that the thiazide doses used in these infusions resulted in plasma concentrations of 11 μg/ml, which is approximately 10–20 times the plasma concentration found in patients clinically treated with thiazides [23,24]. Moreover, these findings were contrary to previous studies, which did not find any vasoactivity in the human forearm, although such studies used doses more comparable to those found in clinical practice [25,26].…”
Section: Antihypertensive Effectsmentioning
confidence: 99%
“…19 Work done by Sudoh et al 20 reveals that concomitant administration of furosemide and lomefloxacin increases the bioavailability of lomefloxacin by decreasing its rate of renal clearance. As quinolones, furosemide and hydrochlorthiazide, 21 are reported to be excreted in urine by the renal tubular anion transport system. Therefore, in present paper, we report a simple, easy, quick and inexpensive isocratic RP-HPLC method with ultraviolet detection at 232 nm for the simultaneous determination of GFX and two diuretics i.e.…”
mentioning
confidence: 99%
“…However, combined administration of candesartan and hydrochlorothiazide increased the bioavailability and C max of candesartan by ∼ 20%, likely related to the competition for secretion by the organic acid tubular secretory pathway in the kidney [59]. Clinically, this effect is compensated by the potentiation of the antihypertensive effect of candesartan by the addition of hydrochlorothiazide [60].…”
Section: Candesartan Cilexitilmentioning
confidence: 99%